Electrochemical reduction of nitroprusside on a glassy carbon electrode modified by poly-L-lysine films - Pereira, Francisco Claudece; Zanoni, Maria Valnice Boldrin [UNESP] (Springer, 2008)
The present work describes the preparation and characterization of polyelectrolyte coatings of poly-L-lysine (PLL) to modify a glassy carbon electrode and its application to the pre-accumulation of nitroprusside (NP). The effects of the coating on the electrochemical reduction of NP were investigated. The performance of the modified electrode indicates that the drug can be immobilized by electrostatic interaction and the voltammetric signal monitored at all pH values in the range of 2-12. The strong interaction between NP and PLL stabilizes the complex on the electrode surface and minimizes the chemical reaction of lost CN- ions as a subsequent reaction of electron transfer, which could improve the action mechanism of NP.
Keywords: sodium nitroprusside; poly-L-lysine; chemically modified electrode